Investigating the effects of sleep and sleep loss on the different stages of episodic emotional memory: A narrative review and guide to the future - Cunningham, Tony J.; Stickgold, Robert; Kensinger, Elizabeth A. (Frontiers in Behavioral Neuroscience, 2022)
For two decades, sleep has been touted as one of the primary drivers for the encoding, consolidation, retention, and retrieval of episodic emotional memory. Recently, however, sleep’s role in emotional memory processing has received renewed scrutiny as meta-analyses and reviews have indicated that sleep may only contribute a small effect that hinges on the content or context of the learning and retrieval episodes. On the one hand, the strong perception of sleep’s importance in maintaining memory for emotional events may have been exacerbated by publication bias phenomena, such as the “winner’s curse” and “file drawer problem.” On the other hand, it is plausible that there are sets of circumstances that lead to consistent and reliable effects of sleep on emotional memory; these circumstances may depend on factors such as the timing and quality of sleep, the content and context of the emotional experience, and the probes and strategies used to assess memory at retrieval. Here, we review the literature on how sleep (and sleep loss) influences each stage of emotional episodic memory. Specifically, we have separated previous work based on the timing of sleep and sleep loss in relation to the different stages of emotional memory processing: (1) prior to encoding, (2) immediately following encoding during early consolidation, (3) during extended consolidation, separated from initial learning, (4) just prior to retrieval, and (5) post-retrieval as memories may be restructured and reconsolidated. The goals of this review are three-fold: (1) examine phases of emotional memory that sleep may influence to a greater or lesser degree, (2) explicitly identify problematic overlaps in traditional sleep-wake study designs that are preventing the ability to better disentangle the potential role of sleep in the different stages of emotional memory processing, and (3) highlight areas for future research by identifying the stages of emotional memory processing in which the effect of sleep and sleep loss remains under-investigated. Here, we begin the task of better understanding the contexts and factors that influence the relationship between sleep and emotional memory processing, and aim to be a valuable resource to facilitate hypothesis generation and promote important future research.